Implementasi Perangkat Internet Gateway Device Untuk Menghubungkan Infrastruktur IoT dan Aplikasi Cloud Menggunakan Narrowband Internet of Things (NB-IoT) - Eric Ferdy Kurniawan; Eko Sakti Pramukantoro; Fariz Andri Bakhtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
IoT architecture can be described with 4 parts, namely sensing, networks, middleware, and application. Generally part of the sensing and middleware are on the intranet, while the application was on the internet as a cloud-based. The condition of the Internet gateway device (IGD) acts as a part of the network architecture that is connecting the IoT middleware in the intranet and internet application in the cloud. IGD function takes the data from the middleware then forwarded to the application cloud. In this research, IGD based network of NB-IoT provide internet connectivity with smaller delay than previous research that uses IGD based network of GPRS. Two test scenarios conducted to measure the delay and throughput data delivery from IGD towards cloud application. In the first scenario, the received sensor data from middleware directly mailed toward the cloud, while the second scenario, the received sensor data from middleware collected and stored first in the JSON file during a span of certain then JSON file is sent towards the cloud. The first scenario test results showed that the mean average delay of 10 seconds and average throughput of 26000bps. Comparison of the test results between second scenario on this research and previous research looks significantly while sending data 2.5Mb data. In previous research, the delay resulted of the delivery 2574984 bytes data of 2818 seconds, while in this research were able to send 2648000 bytes with delay amounted to 22 seconds and average throughput of 97672.742bps.